PENGARUH PELATIHAN KETERAMPILAN KONSELING TERHADAP SIKAP KADER POSYANDU DALAM PELAYANAN KONSELING PENCEGAHAN KANKER SERVIKS DI KABUPATEN KUNINGAN TAHUN 2018 - AI NURASIAH (Ikatan Bidan Indonesia (IBI), 2019)
Cervical cancer is the second leading cause of cancer death in women worldwide after breast cancer, while in Indonesia, cervical cancer ranked first. As many as 15.000 new cases of cervical cancer occur with 7500 mortality cases per year (Depkes RI, 2015). Cervical cancer case in West Java as much as 1,29% in 2016 and 0,24% in Kuningan regency. One of the efforts to suppress the high cases of cervical cancer by providing counselling on basic level i.e. in the community. This effort may involve cadres of Integrated Service Post, because cadres greatly influences the activities that support the health problems. However, the majority of the attitude of Integrated Service Post (Posyandu) cadres in providing counselling are lacking. This research aims to know the influence of reproductive health counselling training against the attitude of Integrated Service Post “Posyandu” cadres in cervical cancer prevention efforts in Kuningan regency. The method of this research uses quasi experiment with design non equivalen comparison group design. The sample of this research is Integrated Service Post “Posyandu” cadres in Bayuning Village as many as 40 people (20 control group and 20 experimental group) with total sampling technique. Data analysis techniques using Paired T-Tes. Bivariat analysis results obtained that there is a difference in attitude on a control group before and after research (0,005), there is a difference in the skills of the experiment group before and after research (p=0,008). Hopefully, the cadres of Integrated Service Post “Posyandu” can be expected to provide counselling to all women of fertile age in order to prevent the occurence of cervical cancer. And Community Health Center “Puskesmas” are able to regularly accompany the Integrated Service Post Cadres and held an examination of early detection of cervical cancer Keywords : Counselling attitude and skill of Integrated Service Post “Posyandu” Cadres